The Many Faces of Osteomyelitis: A Pictorial Review. Issue 1 (11th May 2017) - Desimpel, Julie; Posadzy, Magdalena; Vanhoenacker, Filip
The purpose of this pictorial review is to present an overview of the radioclinical features of osteomyelitis. The presentation of the disease may vary depending on the clinical stage (acute, subacute and chronic), the pathogenesis of the infection and the age of the patient. Thorough knowledge of the basic pathophysiological mechanisms is a prerequisite to understanding the variable imaging appearance of osteomyelitis. Special subtypes of osteomyelitis including CRMO and SAPHO will be discussed very shortly.